2011
DOI: 10.1149/1.3527057
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry and Photocurrent Response from Vertically-Aligned Chemically-Functionalized Single-Walled Carbon Nanotube Arrays

Abstract: The unique electronic properties of single walled carbon nanotubes ͑SWCNTs͒ can be used to generate a current response from visible light. Vertically aligned single walled carbon nanotube arrays were created on an optically transparent electrode ͑fluorine doped tin oxide coated glass, FTO͒ by a self-assembly process using the hydrophobicity of the nanotube side walls and chemical treatment of both the nanotubes and the FTO substrate. The electrode characteristics were explored using electrochemical approaches.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…When the three SWCNT electrodes are irradiated, a negative photocurrent appears at potentials lower than À0.4 V. In previous literature, photoelectroactivity for SWCNTs has been observed in another electrochemical reaction. 56 In our work, the photocathodic process has to be observed at low scan rates (2 mV s À1 ), and the values observed for the photocurrent reached the noticeable value of ca. 20 mA.…”
Section: Photoelectrochemistrymentioning
confidence: 66%
“…When the three SWCNT electrodes are irradiated, a negative photocurrent appears at potentials lower than À0.4 V. In previous literature, photoelectroactivity for SWCNTs has been observed in another electrochemical reaction. 56 In our work, the photocathodic process has to be observed at low scan rates (2 mV s À1 ), and the values observed for the photocurrent reached the noticeable value of ca. 20 mA.…”
Section: Photoelectrochemistrymentioning
confidence: 66%
“…[15][16][17] Very little material was needed to produce a photocurrent, making transparent solar cells possible. Additionally, chemical modification of the SWCNT array by other chromophores, for example dye molecules, 16,18 porphyrins, 19 and also dendrons 20 has led to an increased photovoltaic response. Such devices have been investigated primarily through electrochemistry, studying the surface bound concentration and the electron transfer from the redox-active molecule through the nanotube array to the working electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Transparent vertically aligned SWCNT arrays can be used to generate a prompt and steady photocurrent, 15 and the resultant photoresponse can then be modified by functionalising the array with dye and porphyrin molecules. 18 However, it was found that whilst dye modifying the array increased the current produced, the voltage was decreased. 16,18 One of the most widely studied dendrimer molecules is poly (amidoamine) or PAMAM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon nanotubes (CNTs) are a unique material with many varied applications in the electronics industry such as field emission, 1 electrochemical sensors, 2,3 and photovoltaics. [4][5][6] However, one hindrance to their wide-scale implementation is the ability to produce them both cheaply and with a well-defined structure, both physical and electronic. Current synthesis techniques include arc discharge, 7 laser ablation, 8 and chemical vapor deposition 9 (CVD), with CVD being the most promising approach for high yields.…”
mentioning
confidence: 99%